Soluble Soybean Polysaccharide Improves Quality and Shelf Life of Peanut Butter - Liangchen Zhang; Liyou Zheng; Jian Sun; Sameh A. Korma; Fahad Al-Asmari; Mengxi Xie; Miao Yu (Foods)
Peanut butter, a plant-based spread, has gained global prominence due to the increasing consumer demand for nutritious convenience foods and the rising adoption of plant-based diets. However, oil separation during storage and transportation accelerates the oxidative rancidity and reduces the shelf life of peanut butter. Enhancing peanut butter stability by minimizing oil separation is therefore essential. This study investigates the effect of soluble soybean polysaccharides (SSPSs) on the quality and shelf life of peanut butter. Optimal processing conditions were established by adding 1.7% SSPS (w/w), heating the mixture to 85 °C for 40 min, and then cooling it to 1 °C. The addition of SSPSs significantly increased the lightness of the peanut butter without altering its red-green color characteristics. Furthermore, SSPS incorporation improved its textural properties by increasing hardness and cohesiveness. Nutritional analysis showed that SSPS supplementation elevated proximate composition parameters (moisture, ash, carbohydrates, and fiber) while slightly reducing acid and peroxide values. Scanning electron microscopy revealed that SSPSs enhanced the internal network structure of peanut butter, inhibited oil migration, and reduced centrifugal emulsification rates. First-order kinetic models based on acid and peroxide values were developed to predict the effects of SSPSs on shelf life. Both the model predictions and experimental data confirmed that SSPS addition effectively extends the shelf life of peanut butter.